Mean Number of Non-Growing Ovarian Follicles at Different Age of Bangladeshi Females - A Postmortem Study - Yesmin, Shamima; Anwar, Selina; Begum, Anjum Ara; Ahmed, Neaz; Shah, Md Rabiul Islam (Bangladesh Journal of Anatomy, 2014)
Context: The human ovary contains a fixed number of non-growing primordial follicles maximal at 5th month of gestational age that decreases bi-exponentially with age, culminating in the menopause at an average age of 50-51 years. Number of follicular count is important for determination of ovarian aging. For this reason this study was aimed at determining the mean number of total non-growing follicles in different age groups of Bangladeshi female (cadaver) which will serve as a baseline data for the gynaecologist and obstetrician about the onset of infertility in our country. Materials and Methods: A cross sectional analytical type of study was conducted in the Department of Anatomy of Rangpur Medical College from July 2008 to June 2009. Thirty two ovaries were collected during postmortem from Bangladeshi female aged between 15 and 45 years. The samples were classified into the young (group A- 15-30 years), intermediate (group B 31-38 years) and old (group C - 39-50 years). Three histological slides were prepared from each ovary. Total numbers of non-growing follicles were counted in eight fields of each slide with light microscope. The numbers of follicles were compared between different age groups. Result: Mean number of total ovarian follicles were more in young group, but the number progressively and significantly decreased in intermediate and old groups (P< 0.01 in groups Avs B, P< 0.001 in groups B vs C and P< 0.001 in groups A vs C). Conclusion: From the present study it may be observed that the total follicular number was decreased with increase of age. This may be due to ageing process, hormonal influence, environmental and genetic cause. Estimation of the total number of follicles present in the ovary (ovarian reserve) could be helpful for assisted reproductive techniques such as IVF. Bangladesh J. Anat. 2014; 12(2) : 40-43